Monetary valuation of elite sport policy in Japan using the contingent valuation method: A temporal reliability test - Funahashi, H.; Mano, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
This article reports an application of the contingent valuation method for estimating the monetary value of elite sport policy in Japan. In particular, we tested the temporal reliability issue, which is one of the main limitations reported in the literature, by using a longitudinal survey design. A series of longitudinal questionnaires were administered via an internet-based survey to a sex- and age-stratified random sample of 850 adult Japanese respondents. Baseline assessment took place immediately before the 2012 Summer Olympics (T1: July 2012), with post-assessment (T2: August 2012) and a follow-up 6 months later (T3: February 2013). In each survey, the respondents were asked to state their willingness to pay (WTP) for elite sport policy, which aims to achieve the official target of `The Sports Basic Plan` (i.e. ranking in the top five for the total number of gold medals won in the Summer Olympics and the top ten in the Winter Olympics) in a hypothesised scenario. WTP was elicited using a double-bounded dichotomous-choice approach. Statistical analysis of 613 respondents who completed the entire survey revealed that there were no significant changes in the WTP between the time points. Consequently, the total WTP was reliably estimated to be within the region of ¥50.9-59.3 billion, which was two and half times higher than public elite sport expenditure (around ¥22.7 billion).